THE SCENT OF SAKE: A FAILURE IN THE EMBODIMENT OF JAPANESE WOMAN IDENTITY TO BE AN AUTHENTIC SUBJECT - Zietha Arlamanda Asri; Mira Utami; Sulistya Ningtyas (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
Identity is seen as something important to humans in society, as it shows the origin of the self. Sometimes, someone cannot accept the identity that is attached to them, which will lead to the process of forming a new identity. This case also happens to the main character of The Scent of Sake, a novel by Joyce Lebra published in 2009. Rie Omura is not allowed to interfere in the sake making business, so that she tries to change that identity. Thus, this study aims to examine the process of identity formation that occurs in the character of a Japanese woman, represented by Rie. To answer the research problem, this study uses a textual analysis as the research methods. The theory used to assist the analysis is a perspective proposed by Žižek regarding the formation of subject’s identity to achieve the stage of authentic subject. The results show that in her efforts to unbind herself from the symbolic order, she makes attempts to rule the brewer house. However, her action cannot be categorized as a radical action since it cannot bring her out of the Symbolic. It confirms that Rie is failed to be an authentic subject. Keywords: Japanese Woman, Authentic Subject, Žižek, The Scent of Sake Identitas dipandang sebagai sesuatu yang penting bagi manusia yang hidup bermasyarakat karena menunjukkan asal-usul. Terkadang, seseorang tidak dapat menerima identitas yang melekat padanya, yang akan memantik tindakannya menuju pembentukan identitas baru. Hal ini juga terjadi pada karakter utama dalam novel